Impedance spectra analysis of p-doped organic thin films by charge carrier distribution evaluation - Wißdorf, Victoria; Frericks, Markus; Tzschoppe, Michael; Connor, Paula; Beck, Sebastian; Pflumm, Christof; Pucci, Annemarie; Jaegermann, Wolfram; Mankel, Eric (ACS applied electronic materials, 2019)
We report on a detailed study of the p-doping concentration for two hole transport materials and its influence on current voltage and impedance spectroscopy measurements. The electrical device characteristics show a large increase in current for increasing p-dopant concentration and a clear decrease in asymmetry between forward and backward bias direction. Impedance spectroscopy measurements revealed a dopant concentration dependent capacitance maximum located at zero bias voltage for both materials. With a theoretical approach we perform a quantitative description of the impedance spectroscopy measurements for all p-dopant concentrations. By fitting the measurement data, we are able to determine the doping concentration dependence of the injection barriers, the number of ionized acceptor molecules, the hole mobility, and the charge carrier distribution across the whole device. Furthermore, we are able to explain the dopant concentration dependent capacitance maximum and link it directly to the charge carrier distribution. This approach enables a microscopic interpretation of the impedance spectroscopy measurement results as well as a noninvasive analysis method to study the contact and transport properties of p-doped organic semiconductor films.
Gesehen am 08.10.2020